2002
DOI: 10.1177/003693300204700203
|View full text |Cite
|
Sign up to set email alerts
|

Is There Scope for Checking Serum Biochemistry in the Epilepsy Clinic?

Abstract: We often request blood investigations, almost as a knee-jerk reaction, without asking ourselves why and what we expect to exclude or confirm by doing the test. We often fail to put the patients presentation into clinical perspective. Here, we present a scenario where routine blood tests were unexpectedly abnormal. A patient presents to the First Fit clinic, having sustained two generalised tonic-clonic epileptic seizures. She was commenced on anti-epileptic medication by her GP prior to being seen by the neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Farrugia 5 reports the case of a 45-year-old woman who had sustained two tonic-clonic seizures, and her (purely incidental) blood studies revealed surprisingly low serum calcium. The author emphasizes the importance of biochemistry in studies of patients seen at a “First Seizure Clinic,” despite the fact that, in an overall epileptic population, serum biochemistry is of limited use.…”
Section: Discussionmentioning
confidence: 99%
“…Farrugia 5 reports the case of a 45-year-old woman who had sustained two tonic-clonic seizures, and her (purely incidental) blood studies revealed surprisingly low serum calcium. The author emphasizes the importance of biochemistry in studies of patients seen at a “First Seizure Clinic,” despite the fact that, in an overall epileptic population, serum biochemistry is of limited use.…”
Section: Discussionmentioning
confidence: 99%